2007
DOI: 10.1002/hon.817
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic relevance of circulating matrix metalloproteinase‐2 in acute myeloid leukaemia patients

Abstract: Matrix metalloproteinases (MMPs) were postulated to have important implication in progression and invasiveness of many malignant disorders. On the other hand the biological role of MMP-2 in acute myeloid leukaemia (AML) is not fully clear. Serum samples from 37 adult patients with AML had been taken before chemotherapy was administered. In addition 20 out of the 37 patients were analysed again after achieving complete remission (CR). Ten samples from healthy volunteers were evaluated as the control. Total MMP-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
8
0
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 19 publications
5
8
0
1
Order By: Relevance
“…Importantly, we found that along with the acquisition of drug resistance, there was a marked increase in the expression and activity of MMP-2, which has been known as a marker and key factor in aggressive malignant tumor cells. 7,8,34 In addition to the results from in vitro drug-resistant AML models, invasion assay using primary BM cells supports the suggestion that the elevated level of MMP-2 activity may directly regulate the invasiveness of drug-resistant BM cells. Recently, combined therapy of synthetic MMP inhibitors and anticancer agents has been evaluated to decrease metastasis and improve therapeutic effect in broad range of tumors.…”
Section: Discussionsupporting
confidence: 53%
“…Importantly, we found that along with the acquisition of drug resistance, there was a marked increase in the expression and activity of MMP-2, which has been known as a marker and key factor in aggressive malignant tumor cells. 7,8,34 In addition to the results from in vitro drug-resistant AML models, invasion assay using primary BM cells supports the suggestion that the elevated level of MMP-2 activity may directly regulate the invasiveness of drug-resistant BM cells. Recently, combined therapy of synthetic MMP inhibitors and anticancer agents has been evaluated to decrease metastasis and improve therapeutic effect in broad range of tumors.…”
Section: Discussionsupporting
confidence: 53%
“…In contrast, proMMP-2/-9 patterns were not subtype-restricted. Our data agree with studies in which proMMP-2/-9 levels and FAB subtypes were not correlated [20, 35]. It remains to be seen whether ADAM17 levels are predictive of chemoresistance or responsiveness to treatment in AML.…”
Section: Discussionsupporting
confidence: 91%
“…Several studies have demonstrated the existence of a crosstalk between the endothelium and leukemic cells, in which leukemia cells stimulate BM endothelium and promote de novo angiogenesis and neovascularisation, while BM endothelium promoted leukemia cell survival through modulation of antiapoptotic bcl-2 family members (Veiga et al, 2006). Another study by Aref et al (2007) described in B-ALL an abnormal expression of matrix metalloproteinases (MMP), which is a further class of angiogenesis and tumor progression regulators produced by both stromal and leukemic cells (Aref et al, 2007) A further interesting aspect related to BM microenvironment and leukemia cells interactions regards the role of BM microenvironment on lineage commitment and differentiation. Several studies have indeed demonstrated that BM microenvironment can drive lineagespecific differentiation in leukemia by modulating different cytokines and other soluble components (Kankuri et al, 2008;Wei et al, 2008).…”
Section: Bone Marrow Microenvironmentmentioning
confidence: 99%